2007
DOI: 10.1089/lap.2007.0081
|View full text |Cite
|
Sign up to set email alerts
|

Primary Pull-Through for Hirschsprung's Disease: Comparison of Open and Laparoscopic-Assisted Procedures

Abstract: Rectosigmoid Hirschsprung's disease is usually amenable to minimally invasive primary neonatal pull-through. This may be performed either entirely transanally or with laparoscopic assistance for biopsies with or without colonic mobilization. In our center, all dissection is performed transanally; laparoscopy is used for obtaining colonic biopsies and orientation of the pulled-through bowel segment. In this paper, we describe our initial experience of a consecutive cohort of 20 one-stage laparoscopic-assisted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Thirteen studies 1 , 10 16 , 18 – 21 , 24 reported the number of complications. Analysis of the pooled results also showed that the number of complications was significantly lower in laparoscopic-assisted operations group than in laparotomy operations group (OR = 0.60, 95% CI = 0.40, 0.89) (Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies 1 , 10 16 , 18 – 21 , 24 reported the number of complications. Analysis of the pooled results also showed that the number of complications was significantly lower in laparoscopic-assisted operations group than in laparotomy operations group (OR = 0.60, 95% CI = 0.40, 0.89) (Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…As early as 1994 [7] and 1995 [8] , Smith and Georgeson reported on the Duhamel and Soave procedures assisted by laparoscopy. Subsequently, the Soave operation with laparoscopic assistance has been widely used in the clinic, and remarkable results have been achieved [9][10][11] . We retrospectively analysed clinical data for 186 children with Hirschsprung disease who underwent the Soave operation assisted by laparoscopy in our hospital over 5 years to summarize the experience and clinical e cacy of this approach.…”
Section: Surgical Treatment Is Often Needed In Children With Megacolomentioning
confidence: 99%
“…A 2-3 cm submucosal dissection is done and a 2-3 cm seromuscular cuff is left behind. The aganglionic bowel is then pulled through[1315] the perianal approach and sent for histopathology. The ganglionic bowel is then anastomosed at the dentate line after transecting the aganglionic bowel.…”
Section: Laparoscopymentioning
confidence: 99%